POLITICAL ATTRIBUTES OF CONSTITUTION AND CONSTITUTIONAL ATTRIBUTES OF STATES - Evgeniya Yurtaeva (Sravnitelʹnaâ Politika, 2019)
The article presents an analysis of the political value and social purpose of constitutions as a result of the historical evolution of states and a method of fixing the prospects for political and social development. In particular, questions are raised about the nature of the constitutional act in autocratic states and its social perception. The constitutional characteristics of the constitutional state of rights and justice and social state are subjected to detailed analysis, and their significance is assessed either, in first, as a principle, as a supreme value or a nationwide idea of political development or, in second, as a constitutional legal norm. The author draws attention to the fact that differently formulated constitutional provisions do not give rise to conceptual differences in the law-constitutional practice of states. It has also been noted that not every state that realistically and routinely ensures the rule of law and recognizes the inherent duty of the state to guarantee unconditional basic income as a guarantee of a decent life for citizens, is determined itself constitutional state of rights and justice and social state in its constitution. An important indicator of progressive political and legal development the author sees in the stability of the constitution and legislation. The author believes that there are much more legal grounds for describing the state as constitutional state of rights and justice and social state in constitutions in the form of principles ‒ organizational ideas for creating appropriate conditions, and not as constitutional norms.